2015
DOI: 10.1111/jcmm.12735
|View full text |Cite
|
Sign up to set email alerts
|

Nrdp1S, short variant of Nrdp1, inhibits human glioma progression by increasing Nrdp1‐mediated ErbB3 ubiquitination and degradation

Abstract: The ubiquitin ligase neuregulin receptor degradation protein 1 (Nrdp1) is involved in the induction of apoptosis and suppression of tumour formation. We previously showed that it was expressed at lower levels in human glioma tissues compared with normal brain tissues. However, the mechanism underlying this is unclear. Here, we reported that a novel short variant (Nrdp1S), lacking 71 amino acids at the N‐terminal, was expressed in normal human brain tissue, but absent from glioma tissues. Similar to Nrdp1, Nrdp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…The degradation of intracellular proteins is mainly accomplished by the ubiquitin-proteasome system, and the ubiquitin-proteasome have strong selectivity for protein degradation [ 23 ]. Studies have shown that the ubiquitination pathway is closely related to the occurrence and development of tumors [ 1 , 2 , 8 , 9 , 19 ]. Here we identified six differentially expressed URGs that were related to survival in glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of intracellular proteins is mainly accomplished by the ubiquitin-proteasome system, and the ubiquitin-proteasome have strong selectivity for protein degradation [ 23 ]. Studies have shown that the ubiquitination pathway is closely related to the occurrence and development of tumors [ 1 , 2 , 8 , 9 , 19 ]. Here we identified six differentially expressed URGs that were related to survival in glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we have shown that Nrdp1 is implicated in ischemic cardiomyocyte death, in which overexpression of Nrdp1 augmented ischemia–reperfusion (I/R)-induced cardiomyocyte apoptosis while inhibition of endogenous Nrdp1 could protect cardiomyocytes against I/R injury (Zhang et al, 2011b ). In the brain, Nrdp1 is found to be involved in suppressing brain tumor formation and promoting lipopolysaccharide (LPS)-induced neuroinflammation via its pro-apoptotic action (Shen et al, 2015 ; Shi et al, 2015 ; Wu et al, 2016 ). It is well known that neuronal apoptosis is a major event in ischemic stroke, however, the role of Nrdp1 in ischemic neuronal death has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of specific tumour suppressor genes and activation of specific oncogenes have been demonstrated to be important for the occurrence and malignant progression of glioblastoma . STAT3 has been considered as a valuable therapeutic target in glioma because ( i ) multiple signalling pathways changed in glioma converge to STAT3 and ( ii ) it involves in multiple characteristics of glioma aggressiveness, via regulation of genes especially implicated in cell proliferation, growth, apoptosis, migration, invasion and neoangiogenesis .…”
Section: Discussionmentioning
confidence: 99%